Study on Different Fermentation Condition and Inoculum Concentration in Snake Fruit Vinegar (Salacca zalacca) Production - Zubaidah, Elok (Fakultas Teknologi Pertanian Universitas Brawijaya, 2010)
The objective of producing snake fruit vinegar was to obtain high quality vinegar and improve the effectiveness of first material. This research was aimed to know the effect of alcohol fermentation condition (aerobic and anaerobic) and the effect of inoculation concentration with the Backslop method to the physical, chemical, and sensory characteristics of snake fruit vinegar.This research use Factorial Randomized Block Design with 2 factors, snake fruit vinegar concentration (10%; 15%; 20% b/v) and different fermentation condition (aerobic and anaerobic) with 3 replications. The result of this research showed that fermentation condition during alcohol fermentation and different inoculum concentration gave the significant effect on total acid content and the other parameters. Â Meanwhile the interaction of both factors did not give significant effect. Â Anaerobic condition during alcohol fermentation gave the best resultKeywords: snake fruit vinegar, aerobic, anaerobic, Backslop method, alcohol fermentation